Implementation and Impact of Community Development PT Pertamina Patra Niaga Semambu Eco Farming Program in Semambu Island Village - Doni Paturrahman; Riswani, Riswani; Adinda Putri, Bella (Prospect Publishing, 2024)
Growing awareness of the negative impacts of using chemicals requires a program that is able to change the behaviour of farmers with sustainable agricultural activities. The objectives of this internship are as follows: (1) Participate directly in the implementation of PT Pertamina Patra Niaga Semambu Eco farming community development program in Pulau Semambu Village. (2) Analyze the impact of PT Pertamina Patra Niaga Semambu Eco farming community development program in waste utilization in Pulau Semambu Village The time for this research starts from June 2023 to July 2023. The implementation of this internship is carried out using the method of Active Participation and Direct Observation. The implementation of household-scale organic waste utilization is quite successful to provide awareness for the people of Pulau Semambu Village regarding the use of Organic Waste. With the use of organic fertilizer, Semambu Island Village farmers can save the use of inorganic fertilizer as much as 50kg by cutting monthly costs of Rp.60,000. Semambu Eco farming program has a very good impact on preserving the environment of the agricultural area of Semambu Island Village.